AAV delivery of GBA1 suppresses α-synuclein accumulation in Parkinson’s disease models and restores functions in Gaucher’s disease models - Takuro Okai; Sho Sato; Mugdha Deshpande; Shin-ichi Matsumoto; Miyu Nakayama; Syunsuke Yamamoto; Bettina Strack-Logue; Takeshi Hioki; Maiko Tanaka; Gabriele Proetzel (PLoS ONE, 2025)
Biallelic mutations in the glucosylceramidase beta 1 (GBA1) gene are the underlying genetic cause of Gaucher’s disease (GD), resulting in a deficient lysosomal hydrolase and subsequent accumulation of glycosphingolipids. More recently, GBA1 mutations have been identified as the most prevalent genetic risk factor for Parkinson’s disease (PD), associated with more pronounced symptoms characterized by earlier onset and accelerated cognitive decline. In these GBA-associated PD patients the α-synuclein pathology is more prominent, and recent data suggest a link between α-synucleinopathies and GBA1 mutations. Here, we explored the effect of GBA1 gene supplementation on the GD phenotypes and α-synuclein pathology by using the adeno-associated virus (AAV) system. We have compared two AAV serotypes, AAV5 and AAV9, and two different ubiquitous promoters, and demonstrate that both promoters work efficiently albeit not the same in vitro and in vivo. GBA1 overexpression reduces the accumulation of glucosylsphingosine (GlcSph) and restores motor dysfunction in a GD mouse model. We further demonstrate that GBA1 overexpression can dissolve phospho-α-synuclein aggregation induced by the addition of α-synuclein pre-formed fibril (PFF) in a mouse primary neuron model suggesting the direct effect of β-Glucocerebrosidase (GCase) on α-synuclein accumulation. In vivo, we show that GCase inhibition can induce insoluble high-molecular-weight α-synuclein aggregation and that delivery of GBA1 achieves robust reduction of the α-synuclein aggregates in the mouse brain. In summary, GCase expression not only reduces GlcSph, but also restores GD motor dysfunction and removes α-synuclein aggregates which are the hallmark for PD and α-synucleinopathies. AAV delivery of GBA1 is a powerful approach to restore glucocerebrosidase function and to resolve misfolded α-synuclein protein, with applications for GD and PD.